The Influence of Perceived Ease of Use, Perceived Usefulness and Consumer Satisfaction Towards Online Purchasing Behavior - Adi Irawan Setiyanto; Ahmad Syakir (Journal of Applied Accounting and Taxation, 2019)
This study aims to examine the effect of perceived ease of use, perceived usefulness and consumer satisfaction on online purchasing behavior. This study used 200 respondents taken from the general public living in the area of Batam. The type of data used in this study is the interval scale. Scaling method used in the instrument of Likert scale with 5 rating categories. Data processing techniques in this study using software program SPSS 17. The results of this study indicate that the variables perceived ease of use, variable perceived usefulness, and consumer satisfaction effect on online purchasing behavior either partially or simultaneously. For further research is expected to increase the number of samples, change the sample or add research variables.